Tanycyte ablation in the arcuate nucleus and median eminence increases obesity susceptibility by increasing body fat content in male mice. Issue 10 (16th March 2020) - Yoo, Sooyeon; Cha, David; Kim, Soohyun; Jiang, Lizhi; Cooke, Patrick; Adebesin, Mobolanie; Wolfe, Andrew; Riddle, Ryan; Aja, Susan; Blackshaw, Seth
Abstract: Tanycytes are radial glial cells located in the mediobasal hypothalamus. Recent studies have proposed that tanycytes play an important role in hypothalamic control of energy homeostasis, although this has not been directly tested. Here, we report the phenotype of mice in which tanycytes of the arcuate nucleus and median eminence were conditionally ablated in adult mice. Although the cerebrospinal fluid‐hypothalamic barrier was rendered more permeable following tanycyte ablation, neither the blood‐hypothalamic barrier nor leptin‐induced pSTAT3 activation in hypothalamic parenchyma were affected. We observed a significant increase in visceral fat distribution accompanying insulin insensitivity in male mice, without significant effect on either body weight or food intake. A high‐fat diet tended to accelerate overall body weight gain in tanycyte‐ablated mice, but the development of visceral adiposity and insulin insensitivity was comparable to wildtype. Thermoneutral housing exacerbated fat accumulation and produced a shift away from fat oxidation in tanycyte‐ablated mice. These results clarify the extent to which tanycytes regulate energy balance, and demonstrate a role for tanycytes in regulating fat metabolism. Abstract : Tanycyte ablation resulted in a modest increase of fat mass independent of weight gain and induced insulin resistance. Tanycyte ablation did not significantly affect the blood‐hypothalamus barrier, leptin response in brain, or pituitary hormone levels.